Fine root dynamics across pantropical rainforest ecosystems. (31st May 2021) - Huaraca Huasco, Walter; Riutta, Terhi; Girardin, Cécile A. J.; Hancco Pacha, Fernando; Puma Vilca, Beisit L.; Moore, Sam; Rifai, Sami W.; del Aguila‐Pasquel, Jhon; Araujo Murakami, Alejandro; Freitag, Renata; Morel, Alexandra C.; Demissie, Sheleme; et al.
Abstract: Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions. Abstract : We present the largest global dataset to date on tropical forest fine root biomass, productivity, residence time, and allocation of total net primary productivity to fine roots, collected to a standardised protocol across 47 Global Ecosystems Monitoring plots in lowland and montane forests South America, Africa, and Southeast Asia. We observed large variability in fine root dynamics across sites and between lowland and montane forests. Soil physics and chemistry were the strongest drivers of fine root dynamics, whereas climate variables hardly featured as predictors.